A three-dimensional actively spreading bone repair material based on cell spheroids can facilitate the preservation of tooth extraction sockets - Guo, Xinwei; Zheng, Huimin; Guo, Yusi; Heng, Boon Chin; Yang, Yue; Yao, Weitong; Jiang, Shengjie (Frontiers in Bioengineering and Biotechnology, 2023)
Achieving a successful reconstruction of alveolar bone morphology still remains a challenge because of the irregularity and complex microenvironment of tooth sockets. Biological materials including hydroxyapatite and collagen, are used for alveolar ridge preservation. However, the healing effect is often unsatisfactory. Inspired by superwetting biomimetic materials, we constructed a 3D actively-spreading bone repair material. It consisted of photocurable polyether F127 diacrylate hydrogel loaded with mixed spheroids of mesenchymal stem cells (MSCs) and vascular endothelial cells (ECs). Biologically, cells in the spheroids were able to spread and migrate outwards, and possessed both osteogenic and angiogenic potential. Meanwhile, ECs also enhanced osteogenic differentiation of MSCs. Mechanically, the excellent physical properties of F127DA hydrogel ensured that it was able to be injected directly into the tooth socket and stabilized after light curing. In vivo experiments showed that MSC-EC-F127DA system promoted bone repair and preserved the shape of alveolar ridge within a short time duration. In conclusion, the novel photocurable injectable MSC-EC-F127DA hydrogel system was able to achieve three-dimensional tissue infiltration, and exhibited much therapeutic potential for complex oral bone defects in the future.